Technology Integration in Islamic Religious Education Learning Planning: Policy Framework and Adoption Challenges - Safwandy Nugraha, Mulyawan; Hanna Qodriani, Siti (Yayasan Mentari Madani, 2024)
The purpose of this look at is to determine whether or not the approach for integrating era into Islamic education is a hit and how to get around any limitations that may stand up. This have a look at adopted a descriptive qualitative method. studies that generate descriptive facts from people's written or spoken phrases and perceptible conduct is known as qualitative descriptive research. This studies employed a literary evaluation approach of inquiry. Descriptive analysis turned into used to research the information, looking for tendencies and themes that arose from the substances gathered. The ranges of statistics accumulating, records providing, records condensing, and end-drawing had been used to observe this have a look at. The take a look at's findings suggest that the excellent manner to integrate era into Islamic schooling is by way of enhancing the generation infrastructure, imparting instructors and schooling managers with schooling and expert development possibilities, creating pertinent virtual Islamic content material, and adopting an era-based curriculum method. By way of making technology more broadly to be had, creating generation schooling and certification applications for instructors, diversifying the funding resources for generation integration, and taking a flexible technique to curriculum development and assessment, we can overcome the problems associated with imposing technology integration in Islamic schooling